Legitimacy and Guidance in Upscaling Energy Technology Innovations - Bento, N.; Fontes, M. (Working Papers DINÂMIA'CET, 2021)
The paper aims to improve the understanding about the role of expectations and key innovation processes, such as legitimation and guidance, in the upscaling of low-carbon innovations. We analyze roadmaps developed for floating offshore wind energy to investigate how actors prepare for system growth. We focus on how roadmaps contribute to the formation and sharing of expectations through their influence on system acceptability (legitimacy) and attractiveness (guidance), enabling access to crucial resources. The analysis reveals that institutional and technological context affect guidance, namely a higher external openness as technology matures and governments are involved. An actors’ survey finds that overpromising reduces roadmaps impact on expectations. Analyses of media coverage and Internet searches show that roadmaps affect public perceptions indirectly, through the promotion of experiments. Implications include new directions for conceptualizing legitimacy, guidance and expectations in technological innovation systems, as well as recommendations for managing key processes in systems’ upscaling.